Synthesizing Creative Economy and Religious Moderation: A Bio-anthropological Analysis of Waste Management as the Fulcrum for Empowerment in Matangaji Village - Bambang Ekanara; Maimunah Maimunah; Ilma Riksa Isfiani; Alfian Febriyanto; Ihsan Sa'dudin (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2025)
Abstract: Purpose – This study analyzes the synthesis of creative economy and religious moderation through a community-based waste management program in Matangaji Village, Cirebon. Employing a bio-anthropological framework, this research investigates how the practical activity of waste management functions as a fulcrum for community empowerment. The primary purpose is to dissect the process of transforming waste into valuable products and to understand how this collective economic endeavor becomes a practical venue for internalizing the values of religious moderation. Design/methods/approach – This research utilizes a qualitative method with a case study design. Data were gathered through participatory observation, in-depth interviews, and Focus Group Discussions (FGDs). Findings - The findings reveal that the program not only generates supplementary income through creative recycling but also establishes a social space where values such as cooperation (ta'awun), mutual respect (tasamuh), and environmental stewardship (hifzhu al-bi’ah) are actively practiced. The discussion argues that the tangible economic goal serves as a leverage point that necessitates and reinforces moderate social behaviors. Research Implications - This bio-anthropological analysis concludes that interventions in the physical-biological environment (waste management) are intrinsically linked to the fortification of socio-religious values (anthropological), positioning the program as an effective, replicable model for applied moderation.